The Effectiveness of Using Give One Get One Strategy to Teach Writing - Zahada, Alfa Innersia; Zuhriyah, Mukminatus (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2023)
The purposes of this research were to know the students’ writing skills before and after being taught and to determine whether the use of the Give One Get One strategy significantly affected their writing abilities. This research is a pre-experimental design. The researcher used the one-group posttest pretest design. The pretest was administered before a one-shot case study, a one-group pretest-posttest design, and Intac- treatments were given to the students. The results of the t-test showed the data sig. (2 tailed) is 0.000, the data shows <0.05. If the value of sig. <0.05, then Ha is accepted, H0 is rejected. It can be concluded that Give One Get One is an effective strategy for writing skills for grades VII-G of SMP Negeri 1 Gudo. Hopefully, the teachers can apply this strategy in English classes, and the other researchers can use this research as a reference or comparison and also apply this strategy to other skills and other English subject matter.